Particle shapes on squeezing flow of carreau fluid over a sensor surface - Al Nasrawi, Jaafar Abdul Abbas Abbood; Roslan, Rozaini; Kandasamy, R.; Mohamad, Radiah (IAEME Publication, 2018)
In this research work, we investigated particle shapes flow of Carreau fluid over a sensor surface. Most specifically, the reaction of various parameter namely; power low index, Weissenberg number, squeezing, nanoparticle volume fraction, variation, parndtl numberon temperature in the presence of Cu-engine oil based in the presence of squeezing Carreau flow, which are some of the parameters explored that were not investigated in [1]. We used transformation of similarity to lessen the partial differential equation (PDE) to ordinary differential equations (ODE) for the nonlinear governing equation along with their related boundary conditions. The result of the lessened ODEs is unfolded and explained numerically with the application of the fourth/fifth system Runge-KuttaFehlberg-technique together with procedure and practice of shooting- technique, utilizing Maple 18 code.